TANGGUNG JAWAB KONSULTAN DALAM PEMBUATAN ANALISIS MENGENAI DAMPAK LINGKUNGAN (AMDAL) DI PROVINSI KEPULAUAN BANGKA BELITUNG - Yokotani, Yokotani; Salfutra, Reko Dwi; Wirazilmustaan, Wirazilmustaan (PROGRESIF: Jurnal Hukum, 2016)
The purposes of this research are: first, to identify and analyze the arrangement of the consultant responsibilities in making the AMDAL in Indonesia; second, to analyze and criticize the implementation of the consultant responsibilities in making the AMDAL in Bangka Belitung. Based on these purposes, so the issues that have been discussed are: first, how the arrangement of the consultant responsibilities in making the AMDAL in Indonesia?; second, how the implementation of the consultant responsibilities in making the AMDAL in Bangka Belitung?. To discuss these issues, conducted empirical legal research with the type of research the effectiveness of the law. This research proved, that: first, the consultant responsibilities in making the AMDAL regulated by the Act Number 32 of 2009 years, and the Environment Minister Regulation Number 7 of 2010 years; second, the consultant responsibilities in makin AMDAL will be completed to the extent of agreement with the proponent. Therefore, the recommendations of this research are: first, needed to optimize the enforcement of the Act Number 32 of 2009 years, and the Environment Minister Regulation Number 7 of 2010 years; second, needed more specifically regulation concerning the recognition in makin the AMDAL document.